2022
DOI: 10.20885/ajim.vol4.iss1.art6
|View full text |Cite
|
Sign up to set email alerts
|

Halal blockchain: Bibliometric analysis for mapping research

Abstract: Purpose – The main purpose of this study is to identify patterns and directions of halal blockchain research and find out the development of halal blockchain research trends.Methodology – This study used data from various articles in the Google Scholar database with the publication year limited from 2011 to 2022. Data collection used Harzing's Publish or Perish software. There were 353 articles that matched the keyword and they were processed by bibliometric analysis. Findings – This study found the basic patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our previous work complemented the current research by focusing on a smart contract to record the hash of the fatwa and certificate, which also provides an online verification feature [23]. Since 2019, research in the Halal industry using blockchain technology is still at its infancy stage [24] but has increased over time, as shown by Yanti et al [25] and Tasnim et al [26]. The related works are summarized in Table I.…”
Section: A Related Workmentioning
confidence: 90%
“…Our previous work complemented the current research by focusing on a smart contract to record the hash of the fatwa and certificate, which also provides an online verification feature [23]. Since 2019, research in the Halal industry using blockchain technology is still at its infancy stage [24] but has increased over time, as shown by Yanti et al [25] and Tasnim et al [26]. The related works are summarized in Table I.…”
Section: A Related Workmentioning
confidence: 90%
“…The trend of authorship in this study is shown in Table 1 Next, co-authorship mapping is carried out using VOSviewer software. This mapping discovers the author's collaborative patterns and productivity in writing publications related to specific topics [61]. The results of the co-authorship mapping on AR-MBA topics can be seen in Figure 4.…”
Section: Authorship Patternmentioning
confidence: 91%
“…Furthermore, the search results were also saved as an RIS file for mapping using the VOSviewer application. Bibliometric indicators used in this study [60], represent bibliographic data, such as the number of publications, co-authorships of authors, and citations [61]. Typically, the number of publications measures productivity, and the number of sources measures influence [62].…”
Section: Bibliometric Methodsmentioning
confidence: 99%